Cost overrun in construction projects in developing countries, Gas-Oil industry of Iran as a case study - Derakhshanalavijeh, Roya; Teixeira, Jose Manuel Cardoso (Journal of Civil Engineering and Management, 2017)
Cost overrun in construction projects is a common issue affecting project performance, and Gas-Oil construction projects in Iran are no exception. This paper presents the results of a questionnaire conducted to identify and evaluate the relative importance of the significant factors contributing to the Gas-Oil construction industry of Iran as a case study for developing countries. The survey respondents included project owners, contractors and consultants involved in Iranian Gas-Oil construction projects. The results of the survey revealed that the main causes of cost overrun in this industry include inaccurate cost estimations, improper planning, frequent design changes, inadequate labour/skill availability, inflation of costs of machinery, labour, raw material and transportation prices. The first three factors are the project consultants’ responsibility and the appointment of qualified consultants and personnel training are strongly recommended to alleviate cost overrun. The paper also reviews and compares findings of a set of similar researches in a number of developing countries. First published online: 13 Jul 2016